A Review of Defence Pretrial Disclosures Within the Case Management Theory of Criminal Proceedings in Ghana - Tufuor, Isidore Kwadwo (Journal of Legal Studies, 2022)
This article examines the concept of defense disclosures within the theory of managerialism in criminal proceedings in Ghana. Through a doctrinal and comparative legal analysis with the English jurisdiction, it finds that in substance, the requirement of defense disclosure seeks to move the criminal process from its core protectionist ideology that insulates the accused from matters of proof toward a managerial process informed by objectives of truth-finding, trial efficiency and case management. Ironically, this new direction in the criminal trial process is in practice denounced as being at odds with the procedural due process values that shield the accused from matters of proof and pretrial disclosures. The problem is that unlike in England where the move towards defense disclosures is informed by a clear policy change, the managerial policy introduced by the Judiciary in Ghana is not grounded in any articulated theory or policy direction. While pursuing a path of ensuring effective criminal adjudication through mutual disclosures by the parties, it is important to find a proper balance between the denounced but yet adopted procedural concept of defense disclosures and the highly valued protectionist rights of the accused.